Heureka Group’s growth opportunities in EU markets - Zubovych-Yavorska, Anastasiya (2024)
Thesis is based on a case study of a Czech multinational firm Heureka Group, which provides a comparison website that connects buyers and sellers and includes information about shopper’s behavior. Thesis focuses on growth opportunities in the EU markets for the Heureka Group with the aim of reaching profit and awareness. In the thesis twenty countries in the EU were analyzed for potential expansion with the use of a scoring model. The results from a scoring model showed that Netherlands represents the most favorable conditions among the other nineteen countries in the EU for market entry. Later, the using PESTLE and Porter’s five forces analysis were applied to identify the most suitable form of foreign market entry. From the findings of the methodologies employed the joint venture was chosen as the mode of entry into Netherlands.